2015
DOI: 10.22460/p2m.v2i2p209-216.180
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebutuhan Siswa Dalam Materi Buku Teks Bahasa Inggris Tingkat SMK

Abstract: lainnya. Di SMK, orientasinya adalah mempersiapkan siswa agar mampu berkiprah di dunia kerja. Melihat fenomena di atas, guru-guru Bahasa Inggris di SMK diharapkan memiliki kemampuan dalam menganalisis kebutuhan siswa sehingga mereka dapat merancang proses belajar-mengajar yang sesuai, terutama dalam keterampilan berbahasa Inggris (Listening, Speaking, Reading, dan Writing) dan komponen dalam bahasa Inggris (Grammar & Vocabulary). Tujuan dari penelitian ini adalah untuk mengidentifikasi beberapa informasi faktu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…These majors include: Although many majors are offered, all participants said that English learning in vocational high schools is English in general and not specific to the majors that students 297 take. This statement is similar to the previous research conducted by Cahyati et al (2015), who found that English textbooks of SMK students majoring in TKJ described English material in general and were not directed toward TKJ majors. Supposedly, the primary purpose of teaching English at vocational high schools is to prepare students to master English skills in their major field.…”
Section: Awareness Of Applying Esp Conceptssupporting
confidence: 90%
See 1 more Smart Citation
“…These majors include: Although many majors are offered, all participants said that English learning in vocational high schools is English in general and not specific to the majors that students 297 take. This statement is similar to the previous research conducted by Cahyati et al (2015), who found that English textbooks of SMK students majoring in TKJ described English material in general and were not directed toward TKJ majors. Supposedly, the primary purpose of teaching English at vocational high schools is to prepare students to master English skills in their major field.…”
Section: Awareness Of Applying Esp Conceptssupporting
confidence: 90%
“…The fact it was found that the English learning in SMK is general English learning, not specific for students major. In Cahyati et al (2015), research discovered that English textbooks of SMK students majoring in TKJ more described English material in general and not directed with TKJ majors.…”
Section: Correlation Of Vocational High School and English For Specif...mentioning
confidence: 99%
“…Parents play an important role in helping children carry out assignments given by their teachers, and are required to be technologically literate (Cahyati & Kusumah, 2020).…”
Section: Gladi Jurnal Ilmu Keolahragaan Vol 14 Issue 3 September -288mentioning
confidence: 99%
“…In response to the great demand from the engineering companies, learners have strong needs and motivation to learn English for increasing their English language competence for numerous occupational activities. The learners need English for meeting academic professions and future needs [1].…”
Section: Introductionmentioning
confidence: 99%